'Not a Guarantee of Future Performance': The Local Grammar of Disclaimers. (22nd March 2016) - Cheng, Winnie; Ching, Tiffany
Abstract: The study extends the concept of local grammar to the study of disclaimers in company reports. It also outlines and illustrates an analytical procedure to provide a means of interpreting the local grammar of specific language use. Data analysis has identified 18 functional categories and 13 lexico-grammatical patterns in the disclaimers examined. Functional category labels, including 'creator of disclaimer', 'claim carrier', 'risks', 'nature of thing denied', and 'restriction on dependence/use', were created to directly reflect the discourse functions of the language elements. Based on frequency, the study identifies the canonical pattern, together with its variants, of the local grammar, representing the prototype of the linguistic elements, of the disclaimers. The study contributes to the research of local grammars, affirming the view of previous studies that adopting a local grammar approach, compared with a general grammar, makes analyses of texts of specific language use more simple, precise and useful.